The Influence Of Financial Performance On Audit Delay In Pharmaceutical Companies Listed On The Indonesia Stock Exchange - Naomi Br Lubis; Heriyati Chrisna; Rahima Br Purba (Journal of Management, Economic, and Accounting, 2026)
The research analysis aims to examine the effect of financial performance on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. The research method used is quantitative by analyzing 11 companies in the pharmaceutical sub-sector. The data processing tool used is SPSS version 23. The results of the study indicate that profitability has a negative and significant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. Liquidity has a positive and significant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. Leverage does not have a significant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange. Profitability, liquidity, and leverage have a significant effect on audit delay in pharmaceutical companies listed on the Indonesia Stock Exchange.